A spiritual strategy for cross-cultural mission in Africa : a Chinese missionary's practical proposal - Kritzinger, J.J. (Johan Jakob) (University of Pretoria, 2013)
Thesis (PhD (Science of Religion and Missiology))--University of Pretoria, 2006.